The elasticity and piezoelectricity of AlN containing charged vacancies - Qiaoya Lv; Jian Qiu; Quan Wen (International Journal of Optomechatronics)
Wurtzite aluminum nitride (w-AlN) piezoelectric film plays a key role in modern MEMS actuators and sensors. Density functional theory can be used to predict the elastic and piezoelectric properties of AlN containing various charged vacancies, thereby obtaining methods for improving the piezoelectric properties. The theoretical investigations suggested that the Young’s modulus of defectants are smaller than that of intrinsic AlN, indicating that charged vacancies can effectively improve the elastic properties of AlN. A high piezoelectric coefficient d33 values were obtained in [Formula: see text] [Formula: see text] and [Formula: see text] that may be a cause of the non-symmetrical charges assignation. This work suggests that the elasticity and piezoelectricity of AlN films can be effectively enhancing using the introduction of charged vacancies.